2009
DOI: 10.1007/s00384-009-0705-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal pattern analysis of transcription factor 4 in the developing anorectum of the rat embryo with anorectal malformations

Abstract: These data implied that the downregulation of Tcf4 at the time of cloacal separation into rectum and urethra might be related to the development of ARM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…27 Previous studies have shown that, despite an unclear and complex multifactorial etiology, maldevelopment of the urorectal septum and failure of fusion with the cloacal membrane may underlie ARM. 28 Acting as special types of noncoding RNA molecules, circRNAs can regulate gene expression via miRNA sponges, which indicates that circRNAs may exert a regulatory function in different diseases. 29 However, the expression of circRNAs and their potential regulatory role in ARM have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Previous studies have shown that, despite an unclear and complex multifactorial etiology, maldevelopment of the urorectal septum and failure of fusion with the cloacal membrane may underlie ARM. 28 Acting as special types of noncoding RNA molecules, circRNAs can regulate gene expression via miRNA sponges, which indicates that circRNAs may exert a regulatory function in different diseases. 29 However, the expression of circRNAs and their potential regulatory role in ARM have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, patients with these abnormalities always have severe and long‐term medical problems . Previous studies have shown that, despite an unclear and complex multifactorial etiology, maldevelopment of the urorectal septum and failure of fusion with the cloacal membrane may underlie ARM . Acting as special types of noncoding RNA molecules, circRNAs can regulate gene expression via miRNA sponges, which indicates that circRNAs may exert a regulatory function in different diseases .…”
Section: Discussionmentioning
confidence: 99%
“…ETU-induced ARMs in rat embryos has been previously employed to study the morphological changes of ARMs by several groups, including our laboratory ( Qi, Beasley & Frizelle, 2002 ; Bai et al, 2004 ; Mandhan et al, 2006a ; Mandhan et al, 2006b ; Zhang et al, 2009 ; Wang et al, 2009 ; Tang et al, 2014a ; Tang et al, 2014b ; Zhang et al, 2015 ). In this study, expression of Wif1 in the anorectum showed differences in spatial distribution between normal and ARM embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the etiology of ARMs remains unknown, although several evidences indicated that genetic component involved in the pathogenesis2. Recent studies in animal models with ARMs have greatly enhanced our knowledge in this multifaceted developmental process3,4, which has provided clues to genes and pathways that may be operating in human diseases and in most cases, mutations in the human orthologs give rise to similar or related phenotypes. During the essential period of hindgut development, considerable signaling molecules participated in the embryogenesis of the anorectum, including Wnt5a5,6, Tcf44, Sonic hedgehog (Shh)7,8, Fibroblast growth factor 10(Fgf10)9, Hoxa-13 and Hoxd-1310.…”
Section: Introductionmentioning
confidence: 99%